“Prognostic Significance of Neutrophil‐to‐Lymphocyte, Platelet‐to‐Lymphocyte, and Monocyte‐to‐Lymphocyte Ratios in Myeloid Neoplasms: A Systematic Review” - Mahsa Dabir; Ali Abdolbaghaei; Fatemeh Zoghi; Fatemeh Karpasand; Ali Maleki (Health Science Reports, 2026)
ABSTRACT Background and Aims Myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML) are heterogeneous hematologic malignancies with variable outcomes. Inflammatory markers from routine blood counts, including neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR), and monocyte‐to‐lymphocyte ratio (MLR), have emerged as potential prognostic biomarkers. This systematic review aimed to evaluate their prognostic and diagnostic significance in MDS and AML. Methods A systematic search of PubMed, Web of Science, and Scopus was performed from inception to June 2026. Studies evaluating NLR, PLR, or MLR in MDS or AML were included. Lymphocyte‐to‐monocyte ratio values were converted to MLR using MLR = 1/LMR. Data were synthesized narratively due to heterogeneity. Results Thirteen studies (2847 patients) met inclusion criteria. Elevated NLR, PLR, and MLR were consistently associated with shorter overall survival. NLR showed independent prognostic value in AML and higher‐risk MDS (HR: 1.05–2.136). MLR demonstrated the most consistent prognostic association (cutoffs: 0.20–0.67). PLR showed context‐dependent value (cutoffs: 22.14–213.2). Only one study assessed diagnostic performance, reporting excellent discrimination for NLR (AUC = 0.9169) and good performance for PLR (AUC = 0.8312). Conclusion NLR, PLR, and MLR are accessible biomarkers that may complement risk stratification in MDS and AML. However, heterogeneity in cutoff values limits routine clinical use. Prospective standardized studies are needed to validate these findings.